Biostimulants in dissolved organic matters recovered from anaerobic digestion sludge with alkali-hydrothermal treatment: Nontarget identification by ultrahigh-resolution mass spectrometry. (March 2023) - Du, Zhengliang; Zhao, Peipei; Fu, Qinglong; Wang, Qiandi; Hu, Aibin; Zhang, Weijun; Wang, Dongsheng
Graphical abstract: Highlights: AHT at high pH promoted hydrolysis of protein-like and heterocyclic-N compounds. Harmful aromatics were degraded in AHT at high pH. Increasing pH in AHT improved plant fertility of ADS-derived DOMs. Amino compounds and humic substances are key to promote plant growth. Abstract: Recovering high-value biomaterials from anaerobic digestion sludge (ADS) has attracted considerable attention. However, the molecular features and biological effects of abundant dissolved organic matters (DOMs) in ADS are still unclear, which limits the efficient recycling and application of these bioproducts. This study investigated the molecular composition and transformation of DOMs recovered from ADS through a mild-temperature alkali-hydrothermal treatment (AHT) with ultrahigh-resolution mass spectrometry and energy spectroscopy, and the fertilizing effects of DOMs were evaluated by rice hydroponics. The results indicated that AHT processes significantly promoted the solubilization and release of DOMs from ADS, where most of DOMs molecules remained unchanged and mainly consisted of N-containing compounds with 1–3 N atoms, featuring aromatic or N-heterocyclic rings. Furthermore, AHT processes at pH of 9–10 induced the hydrolysis of partial protein-like substances in DOMs, which was accompanied by formation of heterocyclic-N compounds. Under AHT at pH of 11–12, protein-like and heterocyclic-N substances were increasingly decomposed into amino-N compounds containing 1 or 5 N atoms, while numerous oxygenated aromatic substances with phytotoxicity were degraded and removed from DOMs. Rice hydroponic test verified that ADS-derived DOMs recovered by AHT process at pH of 12 exhibited the highest bioactivity for rice growth, which was attributed to the abundance of amino compounds and humic substances. This study proposed a novel process for the recovery of high-quality liquid organic fertilizer from ADS through AHT process, which can further enrich the technical options available for the safe utilization of sludge resources.